COMPARISON OF EFFECTIVENESS INVENTORY CONTROL OF EOQ METHOD WITH COMPANY METHOD IN STEEL MATERIAL FABRICATION KRAKATAU POSCO - Adam, Gunawan; Tukhas Shilul Imaroh (Dinasti Publisher, 2019)
PT. Krakatau Posco, is the largest steel manufacturing company in Southeast Asia that produces slabs and plates. This study aims to compare the effectiveness of controlling inventory of steel material fabrication workshop with the EOQ method and compared with the current method of the company in an effort to prevent the unavailability of such steel material fabrication. Inventory control using the EOQ method is expected to provide solutions for inventory control, and optimal ordering in order to obtain savings for inventory costs (Total Inventory Cost) at PT. Krakatau Posco. The method used is an interview and take the necessary data, then conduct an initial analysis using the ABC method to clarify the data that has been carried out at PT. Krakatau Posco, controls inventory using EOQ, determines safety stock, ROP and maximum inventory. By controlling the ordering and inventory also expected to provide significant savings for the company, by reducing inventory costs (Total Inventory Cost). The conclusion of this research is the EOQ method is the right method for controlling steel raw material fabrication to meet the production and repair processes at PT. Krakatau Posco and with this method the results of total inventory costs are also more efficient.